(untitled) (Spanish Yearbook of International Law, 2009)
Spanish Law 53/2007 of 28 December on control of overseas trade in defence and dual-use material seeks within the Spanish legal system to regulate a highly delicate matter, namely the fi ght against arms traffi cking, one of humankind’s great scourges as the 21st century commences. The Act has materialised in the context of a very broad-based movement of opinion and regulation that has grown over the last few years in favour of control of sales of defence and dual-use material by international organisations and States, with more emphasis on conventional weapons, trafficking in which poses no less danger than nuclear, biological and other such weapons, known as weapons of mass destruction, which have become the object of growing attention in recent decades. Law 53/2007 contributes two essential elements to the fabric of control over overseas trade in defence and dual-use material: firstly, it takes up all the advances achieved hitherto by regulation and enshrines then in the law; and secondly it establishes parliamentary control of the system’s transparency by obliging the Government to report to the Cortes Generales on its implementation. Nevertheless, certain aspects of Law 53/2007 are open to criticism, for instance an arguably excessive margin of discretion for the JIMDDU as the administrative body in the discharge of certain of its functions, the absence of parliamentary representation on the JIMDDU, or the scant role vouchsafed to the international legal department of the Ministry of Foreign Affairs, which is possibly the government service best equipped to opine on the legality and appropriateness of transfers of defence and dual-use material.